Cross-national variation in faith sharing across religious traditions - Robert D. Woodberry; Matt Bradshaw; Tyler J. Vander Weele; Byron R. Johnson (Scientific Reports)
Abstract Who shares their faith with people who have different religious views? This article examines ‘faith sharing’ across 22 religiously diverse countries. To our knowledge, this is the first study of ‘faith sharing’ across national and religious contexts. Evangelism can be controversial, but both historically and in our data, it is widespread—including in societies that restrict religious liberty. ‘Faith sharing’ is lowest in Europe, Japan, Australia, and the US and highest in Africa, Latin America, the Middle East, and Asia (excluding Japan). Within countries, there is no consistent pattern about which religious groups share their faith more. Previous research about ‘faith sharing’ focuses on Christians in the US, but the factors that predict ‘faith sharing’ in the US often do not generalize. In fact, the association with age, education, marital status, employment status, and immigration status is exactly the opposite in many societies. Because past comparative research ignores this topic and because so much of what we think we know about faith sharing is based on US Christians, we hope this article will spur further research and expand our understanding of religious persuasion and global religious change.